Teaching Undergraduates Research Methods: A "Methods Lab" Approach. Issue 2 (22nd April 2023) - Sullivan, Heather; De Bruin, Erica
ABSTRACT: This article introduces a "methods lab" approach to teaching undergraduates about different types of research in political science. In this approach, students are given explicit instruction on what a specific research method entails and the opportunity to practice it before conducting their own research. Methods labs can help students craft more creative research designs as well as understand the strengths and potential pitfalls associated with each method, making the subsequent process of writing a research paper or thesis easier. We provide two sample methods labs focused on conducting archival research and developing survey and interview questions. We discuss our experiences in implementing the labs in a thesis course, describe how the modular lab approach could fit into multiple types of courses, and offer suggestions for those interested in developing labs for other types of research methods.